Protocol for establishing a core outcome set for evaluation in studies of pulmonary exacerbations in people with cystic fibrosis. Issue 9 (23rd September 2022) - McLeod, Charlie; Smyth, Alan Robert; Messer, Mitch; Schultz, Andre; Wood, Jamie; Norman, Richard; Blyth, Christopher C; Webb, Steve; Elliott, Zoe; Van Devanter, Donald; Stephenson, Anne L; Tong, Allison; et al.
Abstract : Introduction: Pulmonary exacerbations are associated with increased morbidity and mortality in people with cystic fibrosis (CF). There is no consensus about which outcomes should be evaluated in studies of pulmonary exacerbations or how these outcomes should be measured. Outcomes of importance to people with lived experience of the disease are frequently omitted or inconsistently reported in studies, which limits the value of such studies for informing practice and policy. To better standardise outcome reporting and measurement, we aim to develop a core outcome set for studies of pulmonary exacerbations in people with CF (COS-PEX) and consensus recommendations for measurement of core outcomes. Methods and analysis: Preliminary work for development of COS-PEX has been reported, including (1) systematic reviews of outcomes and methods for measurement reported in existing studies of pulmonary exacerbations; (2) workshops with people affected by CF within Australia; and (3) a Bayesian knowledge expert elicitation workshop with health professionals to ascertain outcomes of importance. Here we describe a protocol for the additional stages required for COS-PEX development and consensus methods for measurement of core outcomes. These include (1) an international two-round online Delphi survey and (2) consensus workshops to review and endorse the proposed COS-PEX and to agree with methods for measurement. Ethics and dissemination: National mutual ethics scheme approval has been provided by the Child and Adolescent Health Service Human Research Ethics Committee (RGS 4926). Results will be disseminated via consumer and research networks and peer-reviewed publications. This study is registered with the Core Outcome Measures in Effectiveness Trials database.